Dynamic simulation of taxes and welfare benefits by database imputation - Justin van de Ven; Patryk Bronka; Matteo Richiardi (University of Essex, Centre for Microsimulation and Policy Analysis (CeMPA), 2022)
This paper proposes a new method for imputing taxes and benefits in dynamic microsimulation and agent-based models, which draws upon existing third-party tax-benefit calculators (e.g. EUROMOD). The suggested approach has the advantages of adapting to the degree of related household sector detail described by a model, mitigating computational burden associated with inter-model communications, and permitting taxes and benefits to be imputed directly from commonly available micro-data sources. A practical application of the proposed method is reported for a dynamic programming model designed to reflect the contemporary UK policy context. Reported results indicate that the proposed method for projecting taxes and benefits can imply a comparable computational burden, and generate qualitatively similar results, to a detailed functional description of fiscal policy.
Keywords: 330; Microsimulation; Taxation; Welfare Benefits